Detergent resistant domains in erythrocyte membranes survive after cell cholesterol depletion: an EPR spin label study - Rivas, Maria Gabriela (2003)
We use electron paramagnetic resonance (EPR) with liposoluble spin labels in order to study the lipid structures obtained after Triton X-100 extraction of erythrocyte membranes. The apparent order profile in these detergent resistant membranes (DRM) is very similar to that of the parent membrane, although with higher absolute values, consistent with a liquid-ordered state. DRM could also be obtained from erythrocytes previously depleted in a 40% of their membrane cholesterol, in apparent opposition to the phenomenon of raft disruption reported by other authors. However, the protein profile of these samples showed important differences with that of DRM from untreated cells. The analysis of our results suggests that the effect of Triton X-100 on cholesterol depleted erythrocytes is limited to the solubilization of raft proteins, without disrupting the lipid matrix of DRM.